New records of cacti (Opuntioideae, Cactaceae) for the non-native flora of Tunisia and North Africa with a key to the Cylindropuntieae tribe - El Mokni, Ridha; Verloove, Filip (Mediterranean Botany, 2021)
Botanical surveys undertaken in Central and Northern Tunisia (North Africa), mostly between 2015 and 2020, have revealed three new allochthonous cacti. The reported taxa belong to the genus Cylindropuntia (Cactaceae, subfamily Opuntioideae, tribe Cylindropuntieae). C. leptocaulis, C. prolifera and C. spinosior are here reported for the first time from North Africa. Updated nomenclature, descriptions, general and national distributions are pointed out for each species. An analytical key and field photographs are also provided.